Hepatitis B virus (HBV)‐infected patients with low hepatitis B surface antigen and high hepatitis B core‐related antigen titers have a high risk of HBV‐related hepatocellular carcinoma. Issue 1 (27th December 2018) - Suzuki, Yuichiro; Maekawa, Shinya; Komatsu, Nobutoshi; Sato, Mitsuaki; Tatsumi, Akihisa; Miura, Mika; Matsuda, Shuya; Muraoka, Masaru; Nakakuki, Natsuko; Shindo, Hiroko; Amemiya, Fumitake; Takano, Shinichi; et al.
Abstract : Aim: Although the viral markers hepatitis B surface antigen (HBsAg) and hepatitis B core‐related antigen (HbcrAg) could reflect intrahepatic hepatitis B virus (HBV) replication activity and constitute important biomarkers for hepatocellular carcinoma (HCC), the value of using these two markers in combination for assessing HCC risk has not been clarified in detail. Methods: Four hundred and forty‐nine consecutive patients with chronic HBV infection were included in the study and the association of HBsAg and HBcrAg with HCC risk was investigated cross‐sectionally, as well as longitudinally. Results: When the high value cut‐offs of HBsAg and HBcrAg were defined as 3.0 log IU/mL and 3.0 log U/mL, respectively, patients with a history of HCC were found frequently in the low HBsAg group ( P  = 0.002) and high HBcrAg group ( P  < 0.001). When HBsAg and HBcrAg were combined, an HCC history was most frequent in the subset with low HBsAg and high HBcrAg, among the HBeAg‐negative patients (odds ratio [OR], 7.83; P  < 0.001), irrespective of nucleos(t) ide analogue (NA) therapy (NA: OR, 4.76; P  < 0.001; non‐NA: OR, 9.60; P  < 0.001). In a longitudinal analysis of the subsequent development of HCC, carried out on the 338 patients without an HCC history at enrollment, HCC developed significantly more frequently in the low HBsAg/high HBcrAg group ( P  = 0.005). Conclusions: Patients with low HBsAg/high HBcrAg values are at high risk of developing HBV‐related HCC, according to this cross‐sectional and longitudinal analysis, indicating that the combination of HBsAg and HBcrAg values is an excellent biomarker for assessing HCC risk.